2021
DOI: 10.1371/journal.pntd.0008964
|View full text |Cite
|
Sign up to set email alerts
|

Fat tissue regulates the pathogenesis and severity of cardiomyopathy in murine chagas disease

Abstract: Chronic Chagas cardiomyopathy (CCC) caused by a parasite Trypanosoma cruzi is a life-threatening disease in Latin America, for which there is no effective drug or vaccine. The pathogenesis of CCC is complex and multifactorial. Previously, we demonstrated T. cruzi infected mice lose a significant amount of fat tissue which correlates with progression of CCC. Based on this an investigation was undertaken during both acute and chronic T. cruzi infection utilizing the FAT-ATTAC murine model (that allows modulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…Indeed, previously we 5 demonstrated that pathogens like T. cruzi and Mycobacterium tuberculosis persists in WAT and that loss 5 of fat cells increases the risk of disease manifestation. For example, we showed that loss of body fat 5 correlated to increased cardiomyopathy in chronic Chagas disease murine model and increased pulmonary 5 pathology in aerosol infected TB murine model [20,22]. Our current study suggests that WAT may serve 5 as a reservoir for CoV2, sparing the lungs from the viral burden and infection severity.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Indeed, previously we 5 demonstrated that pathogens like T. cruzi and Mycobacterium tuberculosis persists in WAT and that loss 5 of fat cells increases the risk of disease manifestation. For example, we showed that loss of body fat 5 correlated to increased cardiomyopathy in chronic Chagas disease murine model and increased pulmonary 5 pathology in aerosol infected TB murine model [20,22]. Our current study suggests that WAT may serve 5 as a reservoir for CoV2, sparing the lungs from the viral burden and infection severity.…”
Section: Discussionmentioning
confidence: 73%
“…Tissue lysates were prepared as previously described [20]. Each sample containing 30 μ g of protein were 1 resolved on SDS-PAGE and separately on native gel electrophoresis and the proteins were transferred to 1 nitrocellulose membrane for immunoblot analysis.…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Using a FAT-ATTAC murine model, in which mice were inoculated intra-peritoneally with trypomastigotes to cause acute and chronic disease, Lizardo et al [60] demonstrated the correlation of Chronic Ch-CMP progression to lose adipose tissue. During the acute phase, increased lipid accumulation in myocardial cells, infiltration of immune cells and elevated number of parasites was reported.…”
Section: T Cruzi Infection Models To Understand Tissue Tropismmentioning
confidence: 99%